Petroleum Prospects under the Lotikipi Basin, North-Western Kenya - Rop , Bernard Kipsang (African Journal of Education,Science and Technology (AJEST), 2013)
The assumption that sedimentary rock sequences of Mesozoic age, similar in age to the Jurassic-Cretaceous sequence of southern Sudan, where oil pools have been discovered, under the vast alluvial plains of the little known Lotikipi Basin (NW Kenya) formed the premise of the study. A new interpretation of the gravity and seismic data, preserved in the National Oil Corporation of Kenya (NOCK) records, bolster the possibility that under the thick cover of weathered volcanic rocks and alluvium lie sedimentary sequences ( 1050-2100 m thick) which may be suitable for hydrocarbon exploration. Since the beginning of the Cretaceous, the Lotikipi Basin seems to have evolved consequent to a complex tectonic activity related to continental drifting and block faulting of the Anza and Central African Rift Systems.